2019
DOI: 10.1111/acer.13950
|View full text |Cite
|
Sign up to set email alerts
|

Inulin Ameliorates Alcoholic Liver Disease via Suppressing LPSTLR4‐Mψ Axis and Modulating Gut Microbiota in Mice

Abstract: Background: Alcoholic liver disease (ALD) represents a chronic liver disorder caused by alcohol abuse. Numerous studies have demonstrated that gut microbiota dysbiosis plays a critical role in ALD pathogenesis. Application of prebiotic, probiotic, and dietary supplementation to the modulation of gut microbiota contributes to a novel approach to the management of ALD. Inulin, a natural prebiotic found in plants, can restore gut dysbiosis in ALD. However, the exact mechanism of dietary inulin in ALD remains larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 48 publications
5
44
2
Order By: Relevance
“…Increased studies have shown that INU attenuates metabolic disorders through improving serum lipid, fasting blood glucose and insulin resistance with restoring gut microbiota composition (Zhu et al, 2017;Zou et al, 2018;Misiakiewicz-Has et al, 2019;Song et al, 2019). Our previous studies also demonstrated the amelioration of INU on chronic metabolic diseases (Li et al, 2019;Xue et al, 2019;Yang et al, 2019). However, the effects and mechanism of INU on NAFLD are largely unclear.…”
Section: Introductionmentioning
confidence: 83%
“…Increased studies have shown that INU attenuates metabolic disorders through improving serum lipid, fasting blood glucose and insulin resistance with restoring gut microbiota composition (Zhu et al, 2017;Zou et al, 2018;Misiakiewicz-Has et al, 2019;Song et al, 2019). Our previous studies also demonstrated the amelioration of INU on chronic metabolic diseases (Li et al, 2019;Xue et al, 2019;Yang et al, 2019). However, the effects and mechanism of INU on NAFLD are largely unclear.…”
Section: Introductionmentioning
confidence: 83%
“…Then, the cotton swab with vaginal secretions was taken out and separated by aseptic scissors as well as stored at −80 • C immediately for subsequent DNA extraction. The protocols for sample processing, 16S ribosomal DNA gene amplification, sequencing, and statistical analysis of microbiota data were performed as described previously (43).…”
Section: Gut Microbiota and Vmb Sequencing Analysismentioning
confidence: 99%
“…Inulins, linear carbohydrate polymers that consist of β-(2, 1) fructosyl-fructose linkages, are widely added to dairy products, such as milk drinks and desserts. Because of their selective fermentation feature in the colon, inulins exhibit different characteristics from most dietary fibers 2 ; thus, they show beneficial effects through several gastrointestinal functions, including increasing mineral absorption 3 and systemic immunity 4 , as well as decreasing the risks of intestinal infections 5 , liver diseases 6 , colon cancer 7 , type II diabetes 8 and obesity 9 .…”
Section: Societal Lifestyle Changes Especially Increased Consumptionmentioning
confidence: 99%